Sport as compensation for infantile traits in young people - I.S. Krutko; Kadrik A.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the relationship between sports activity and infantilism traits using the example of sports youth. Methods and structure of the study. The scientific work was carried out in Yekaterinburg, in the fall of 2023. The target group of the study is students of the Institute of Physical Culture, Sports and Youth Policy of UrFU, bachelors and masters, n=42, age from 19 to 23 years. A formative experiment was conducted in which non-athlete students attended mindfulness training sessions that included a unit on motivation to play sports, and they actively attended various sections, kept a diary, and reported. At the end of the experiment, infantile traits were measured in the group of «non-athletes» in December 2023. Results and conclusions. As the study showed, medium and high levels of infantilism are associated with protective mechanisms of denial, regression and compensation, and low subjective control. In the group of athletes studied, infantile traits are less pronounced and are associated with intellectualization, reactive formations and projection. The influence of sports activity on the control group of «non-athletes» led to a decrease in infantilization. It can be stated that infantile traits in young people are a spontaneous adaptation mechanism that is controlled through sport as a special activity that can act as a factor in the compensation of infantile traits, including the mechanism of infantilism on an unconscious level, making it irrelevant.